Peran Filsafat Islam pada Lembaga Pendidikan Islam Madrasah Ibtidaiyah Miftahul Huda Bonangrejo: Studi Analisis Ontologi, Epistemologi, dan Aksiologi Tahun 2025 - Mujiburrohman, Mujiburrohman; Isrofuzain, Isrofuzain (Lembaga Yasin AlSys, 2025)
This research aims to analyze the role of Islamic educational philosophy in shaping the learning system and practices at MI Miftahul Huda Bonangrejo through ontological, epistemological, and axiological approaches. The main focus is on how understandings of the nature of reality (ontology), the sources and processes of knowledge (epistemology), and values and life purposes (axiology) are internalized within the madrasah’s curriculum, teaching strategies, and institutional culture. The study employs a qualitative method, with data collected through in-depth interviews with the head of the madrasah and teachers, participatory classroom observations, and curriculum document analysis. The findings reveal that the ontological dimension is reflected in the recognition of God, human beings, and nature as interconnected creations within the learning system. The epistemological aspect is evident in the integration of revelation and reason as sources of knowledge, embedded in instructional content and dialogical, reflective teaching methods. Meanwhile, the axiological aspect is implemented through values such as honesty, responsibility, and spirituality, which are cultivated in students’ daily lives. The study concludes that the philosophical foundations of Islam are not only relevant but also applicable in shaping the character and intellectual development of students in Islamic primary education. The implications highlight the importance of strengthening philosophical dimensions in curriculum development and educational culture within madrasahs.